The impact of policy initiatives on the design of public spaces on the example of the New European Bauhaus - Woźniczka, Agata (Wpływ inicjatyw politycznych na projektowanie przestrzeni publicznych na przykładzie Nowego Europejskiego Bauhausu, 2023)
The program of contemporary public spaces continues to add new functions. As is the awareness of using the design of common spaces to speculate on property values, the use of architecture and public spaces of the second decade of the 21st century as political paraphernalia – used by both civic initiatives and official administrative bodies – is also growing in popularity. The author’s goal in this paper was to examine the impact of political initiatives on public spaces, and because of the timeliness and multifaceted ambitions of the New European Bauhaus (NEB), it was this initiative that was chosen for analysis. The paper describes the implementation potential of the NEB Compass, a tool that the New European Bauhaus initiative is currently proposing as a concrete aid to realizing abstract ambitions. During the research , an extensive literature study of the subject was carried out, which provided an overview of official EU documents describing the New European Bauhaus initiative and the principles of the NEB Compass. The “research by design” method was then used to transform the Compass from an evaluation system into an instrument for formulating design guidelines. The studied multimodal interchanges of the city of Warsaw and the guidelines for their revitalization, formulated through the NEB Compass, showed that an audit tool can be transformed into a design instrument. Testing the resulting evaluation sheet in a project on transforming Warsaw’s interchanges into sustainable and inclusive public spaces made it possible to define effective ways of transforming urban infrastructure into public space, and to diagnose the potential impact of the chosen policy initiative on shaping contemporary public spaces.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 81-92
Keywords: architektura; sustainability; New European Bauhaus; public space; multifaceted design; design tools; zrównoważenie; Nowy Europejski Bauhaus; przestrzeń publiczna; projektowanie wieloaspektowe; narzędzia projektowe